Point of Sale Tobacco Marketing to Youth in New York State - Waddell, Elizabeth Needham (J Adolesc Health, 2016)
PURPOSE: To assess youth exposure to menthol versus non-menthol cigarette advertising, we examined whether menthol cigarette promotions are more likely in neighborhoods with relatively high youth populations. METHODS: We linked 2011 New York State Retail Advertising Tobacco Survey observational data with US Census and American Community Survey demographic data. Multivariable models assessed the relationship between neighborhood youth population and point-of-sale cigarette promotions for three brands of cigarettes, adjusting for neighborhood demographic characteristics including race/ethnicity and poverty. RESULTS: Menthol cigarette point-of-sale marketing was more likely in neighborhoods with higher proportions of youth, adjusting for presence of non-menthol brand marketing, neighborhood race/ethnicity, neighborhood poverty, and urban geography. CONCLUSION: Data from the 2011 RATS study linked to block level census data clearly indicate that price reduction promotions for menthol cigarettes are disproportionately targeted to youth markets in New York State.